Bird records from the rural landscape of Igarapé-Açu municipality, Northeastern Pará - Stefan Hohnwald (Boletim do Museu Paraense Emílio Goeldi. Ciências Naturais, 2009)
This paper reports on bird records from the little studied Bragantina region, in the densely populated Northeastern Amazon. This region was a center of human colonization in the last century, resulting in the nearly complete replacement of rainforests by a dynamic, mosaic-like rural landscape pattern. From February 1999 to January 2001, I surveyed birds at three sites: a 25-ha smallholding farm, and around two small lakes, in the municipality of Igarapé-Açu. Bird species were recorded along 36 days during an agricultural experiment. As would be expected, species lists from these sites show reduced bird diversity in comparison to primary forests. They also reveal a preponderance of robust, widespread generalists, such as Crotophaga ani (Linnaeus, 1758), Ramphocelus carbo (Pallas, 1764), and Columbina passerina (Linnaeus, 1758). However, endemic Xipholena lamellipennis (Lafresnaye, 1839), Tachybaptus dominicus (Linnaeus, 1766), and Primolius maracana (Vieillot, 1816) (high count of 34 at one time), were also observed. In all, 110 bird species (representing 95 genera and 40 families) are listed with information about abundance and habitat. More detailed surveys of this region are recommended, which should focus on gallery forests that might serve as refuges for some forest species.